Duplicity or Discernment?: Code-Switching and Religious Identity - Little, Sabrina (Philosophia Christi, 2024)
Code-switching is the adjustment of one's speech, behaviors, or appearance across various contexts. Sometimes we code-switch to adapt to the communication norms of different groups, and sometimes we code-switch from social necessity. In many cases, code-switching is not morally blameworthy. It demonstrates an agent's discernment or practical wisdom in navigating various situations. However, not all cases of code-switching are compatible with a good moral character. Many cases of code-switching involve a kind of impression management or doublespeak that can compromise integrity. This article examines the conditions under which code-switching is duplicitous. More specifically, it explores code-switching regarding theological identity and plausible psychological and spiritual repercussions of code-switching for the agent.